The Role of Engaged Scholarly Relationships in Enhancing the Pedagogy of Reading Proficiency - Mukhari, Shirley S.; Sanders, Debbie A. (Journal of Teaching and Learning, 2025)
In recent years there has been a growing trend of academics and teachers collaborating in complementary associations. This is often achieved through engaged scholarship projects such as those which aim to enhance learners’ reading skills. A comprehensive review of the literature underscores the importance of pedagogical support in cultivating effective reading skills, with numerous engaged scholarship relationships focusing on reading-related support, in an effort to meet this need. This study investigated the essential role of engaged scholarly relationships in advancing pedagogical approaches to the teaching of reading. A qualitative participatory-action research approach was adopted, which enabled the researchers to interview thirteen (13) primary school language teachers who were purposively selected for their experience and expertise in this field. Through interviews, the researchers investigated the pivotal role of engaged scholarship projects in supporting the teaching and learning of reading. The findings are relevant in that they bear testimony to the success of implementing engaged scholarship projects for improving the teaching and learning of reading. The researchers conclude that engaged scholarship projects enhance the teaching and learning of such skills, provided that certain challenges are addressed, and strategies are implemented to support their progress.